Neoadjuvant Treatments for Advanced Resectable Melanoma. Issue 2 (27th December 2018) - Liu, Jessica Y; Lowe, Michael
Abstract : Neoadjuvant therapy has demonstrated promise as a treatment modality in resectable advanced‐stage melanoma. Treatment has evolved beyond chemotherapy, with the utilization of biochemotherapy, immunotherapy, and targeted therapy in the neoadjuvant setting. These therapies have shown better progression‐free survival and melanoma‐specific survival when compared with patients that proceed directly to surgery. Ongoing clinical trials will continue to propel research forward to improve the available options for patients with resectable advanced regional disease.